Humane Education for Students with Visual Impairments: Learning about Working Dogs. (July 2015) - Bruce, Susan M.; Feinstein, Jennie Dapice; Kennedy, Meghan C.; Liu, Ming
Introduction: This study examined the effect of an animal-assisted humane education course on the knowledge of students about caring for dogs physically and psychologically and making informed decisions about dog ownership, including working dogs. Method: This collaborative action-research study employed case study design to examine the effect of an eight-week animal-assisted humane education course on the knowledge and skills of four secondary students with visual impairments. Two independent raters applied constant comparative analysis for all of the following data sources: pre- and postintervention interviews, pre- and postintervention tests, videotaped observations, and field notes. Findings were determined for individual students and the class as a whole. Results: The greatest gains made by students included learning how to greet, feed, play with, obtain, and pay for dogs; they also learned about appropriate equipment and the roles of working dogs. Effective instructional strategies included assessing prior knowledge and experience with dogs, practicing skills, using tactile techniques, using routines and repetition, and correcting misconceptions. Discussion: Findings indicate that although students did not master all of the knowledge and skills taught in the course, they became more knowledgeable about care and ownership of dogs. Limitations of this study are the small sample size and short intervention time. Future research may feature longer intervention periods and make connections between humane education, orientation and mobility, and the core content areas of science and mathematics. Implications for practitioners: Students with visual impairments must be provided with experiences with different types of working dogs. Ample time should be given to explore equipment and to practice skills that are essential to responsible care and ownership of dogs.